Wer hat Zugang zu Elterngeld? Soziale Rechte und Anspruchsbedingungen in vergleichender Perspektive - Blum, S; Dobrotić, I (Duncker and Humblot, 2018)
There is limited knowledge about eligibility for leave benefits in general, and about leave rights of parents less securely attached to the labour market in particular. Consequently, social inequalities in access to leave benefit rights remain hidden, which may be particularly pronounced in countries where a certain duration or form of employment is a principal condition to exercise leave rights. In this chapter, we develop an innovative conceptual framework based on the social rights literature, which takes into account how access to parental leave benefits is granted (in-)dependent of labour market position. Four ideal types are presented: the universal parenthood model, the selective parenthood model, the universal adult-worker model, and the selective adult-worker model. Finally, we illustrate these types with three country case of parental leave systems: Germany, Belgium, and Croatia.